Thermal energy storage in building integrated thermal systems: A review. Part 2. Integration as passive system. (January 2016) - Navarro, Lidia; de Gracia, Alvaro; Niall, Dervilla; Castell, Albert; Browne, Maria; McCormack, Sarah J.; Griffiths, Philip; Cabeza, Luisa F.
Abstract: Energy consumption trends in residential and commercial buildings show a significant increase in recent decades. One of the key points for reducing energy consumption in buildings is to decrease the energy demand. Buildings envelopes are not just a structure they also provide protection from outdoor weather conditions always taking into account the local climate. Thermal energy storage has been used and applied to the building structure by taking advantage of sensible heat storage of materials with high thermal mass. But in recent years, researchers have focused their studies on the implementation of latent heat storage materials that if well incorporated could have high potential in energy demand reduction without occupying the space required by sensible storage. The aim of this study is to review the thermal energy storage passive systems that have been integrated in building components such as walls, ceilings or floors, and to classify them depending on their component integration. Highlights: TES could be integrated in buildings envelope using sensible or latent heat method. Solar walls registered highest energetic benefits in sensible heat storage systems. PCM incorporation depends on the method used and where the material is embedded. Wallboards with 25% or less PCM registered low effect and not economically feasible. Macro-encapsulated PCM higher potential and no materials incompatibility problems.